Electrocardiogram Standards for Children and Young Adults Using Z-Scores. (August 2020) - Bratincsák, András; Kimata, Chieko; Limm-Chan, Blair N.; Vincent, Kevin P.; Williams, Matthew R.; Perry, James C.
Abstract : Background: Normative ECG values for children are based on relatively few subjects and are not standardized, resulting in interpersonal variability of interpretation. Recent advances in digital technology allow a more quantitative, reproducible assessment of ECG variables. Our objective was to create the foundation of normative ECG standards in the young utilizing Z -scores. Methods: One hundred two ECG variables were collected from a retrospective cohort of 27 085 study subjects with no known heart condition, ages 0 to 39 years. The cohort was divided into 16 age groups by sex. Median, interquartile range, and range were calculated for each variable adjusted to body surface area. Results: Normative standards were developed for all 102 ECG variables including heart rate; P, R, and T axis; R-T axis deviation; PR interval, QRS duration, QT, and QTc interval; P, Q, R, S, and T amplitudes in 12 leads; as well as QRS and T wave integrals. Incremental Z -score values between –2.5 and 2.5 were calculated to establish upper and lower limits of normal. Historical ECG interpretative concepts were reassessed and new concepts observed. Conclusions: Electronically acquired ECG values based on the largest pediatric and young adult cohort ever compiled provide the first detailed, standardized, quantitative foundation of traditional and novel ECG variables. Expression of ECG variables by Z -scores lends an objective and reproducible evaluation without interpreter bias that can lead to more confident establishment of ECG-disease correlations and improved automated ECG readings in high-volume cardiac screening efforts in the young. Abstract : Supplemental Digital Content is available in the text.